David Stanfield's contribution to the comparative study of the Canon of Lekë Dukagjini and the Canon of Dagestan - Muhadri, Besim (Technium Social Sciences Journal, 2023)
The Albanian monumental work The Canon of Lekë Dukagjin, or the Albanian Canon, is among the unique works with a humanistic spirit of the European Renaissance period, but also of the entire Albanian ethnoculture. The interests of foreign scholars in the study of this important document are early, but they will intensify especially after its publication as a book in 1933, to continue to the present day. In addition to Europe, studies on the Albanian Code will be "relocated" to the United States and Japan. In 1996, an interesting study by the Albanian professor Muharrem Dragovaja was published, entitled "Comparative study of the Code of Albania and Dagestan", which provides in detail comparative data on the main customary rights of the Code of Lekë Dukagjini in Albania and the Code of Dagestan in Dagestan. A valuable contribution to the coming to light of this study, undoubtedly has David Stanfield. In his comparative study between the Code of Lekë Dukagjini the Code of Dagestan, Professor M. Dragovaja, where he has examined aspects related to: Family, Marriage, Inheritance, Property, Border, Land Market, Honor and Blood feud etc., where, he has drawn some important findings. The comparisons drawn in this study give readers the opportunity to draw “conclusions about common curious elements that have evolved into customary rules of conduct and customs in mountainous Christian and Islamic communities from countries as far away as the Caucasus and the Balkans.